Neutrophil extracellular traps in bacterial infections and evasion strategies - Baz, Ahmed Adel; Hao, Huafang; Lan, Shimei; Li, Zhangcheng; Liu, Shuang; Chen, Shengli; Chu, Yuefeng (Frontiers in Immunology, 2024)
Neutrophils are innate immune cells that have a vital role in host defense systems.Neutrophil extracellular traps (NETs) are one of neutrophils' defense mechanisms against pathogens. NETs comprise an ejected lattice of chromatin associated with histones, granular proteins, and cytosolic proteins. They are thought to be an efficient strategy to capture and/or kill bacteria and received intensive research interest in the recent years. However, soon after NETs were identified, it was observed that certain bacteria were able to evade NET entrapment through many different mechanisms. Here, we outline the recent progress of NETs in bacterial infections and the strategies employed by bacteria to evade or withstand NETs. Identifying the molecules and mechanisms that modulate NET release will improve our understanding of the functions of NETs in infections and provide new avenues for the prevention and treatment of bacterial diseases.